Designing a Digital Library System Using the Zachman Framework: A Case Study at Gajayana University - Muchamad Alfan A.P; Arifin Bukhori; Fachrudin Pakaja (International Journal of Information Systems and Technology, 2025)
Abstract- Digital libraries are one alternative to conventional libraries. This design offers digital-based library services. In its development, the digital library information system faces several challenges common in the context of user knowledge. This study aims to design an enterprise architecture for a digital library information system using the Zachman Framework as a systematic approach that accommodates various stakeholder perspectives. The method involves mapping six perspectives (from Planner to Subcontractor) against the six aspects of 5W+1H. The design results show that the Zachman approach can provide a comprehensive overview of the system's data structure, network, actors, operational time, and motivation in a structured and integrated manner. As a result, this design can be used as a reference for the development of digital library information systems in the future and improve operational effectiveness with other users.   This design aims to increase transparency in the distribution of functional responsibilities so that users with interests can understand their roles more clearly in the digital library work system. In addition, the proposed system contributes to optimizing operational processes, reducing problems that previously occurred in conventional libraries, and enabling faster, more efficient, and integrated information and service management.